Analisis Ekonometrika Metode Error Correction Model (ECM) Peran Konsumsi Rumah Tangga, Pengeluaran Pemerintah, Investasi, dan Ekspor Netto Terhadap Pertumbuhan Ekonomi di Indonesia - Purnomo, Agus (Yayasan Sagita Akademia Maju, 2025)
The aim of writing this article is to publish research results related to the role of household consumption, government spending, investment and net exports in influencing economic growth in Indonesia during the 2010-2023 period on a quarterly basis. Econometric analysis using the Error Correction Model (ECM) method is used to test linear regression between the independent variable and the dependent variable. The quantitative data in this research is in the form of secondary data obtained from statistical reports on the websites of the Central Statistics Agency of the Republic of Indonesia (BPS RI), Ministry of Trade of the Republic of Indonesia, Bank Indonesia, Financial Services Authority of the Republic of Indonesia and several related agencies. The results of this research show that together the independent variables consisting of household consumption, government spending, investment and net exports have an effect on economic growth, both in the long and short term. Over the long term, partially the variables household consumption, investment and net exports are positively and significantly correlated with economic growth. Meanwhile, government spending has a negative but not significant correlation with economic growth. For the short term, partially all independent variables in the form of household consumption, government spending, investment and net exports are positively and significantly correlated with economic growth.